Association of HIV/AIDS Clinician Warm Line Utilization with Diagnosis and Management of Antiretroviral Treatment Failure in Mozambique: A Retrospective Analysis of Program Data - Ruano Camps, Maria (J Int Assoc Provid AIDS Care, 2017)
In accordance with global HIV/AIDS goals, Mozambique is attempting to improve management of antiretroviral treatment failure (TF). We sought to determine whether the utilization of a national HIV/AIDS clinician telephone consultation service increased recognition and reporting of TF. In a retrospective analysis of routinely collected program data from telephone consultation logs and Mozambique’s national registry of second-line antiretroviral requests, we used linear mixed methods to describe the association between TF-related telephone consultations and submission of second-line requests, which required documentation of the TF diagnosis. The unit of analysis was the health facility. Available data included 1417 consultations (390 [27.5%] TF related) and 2662 second-line requests from 1011 health units (2015-2016 data). In multivariable analyses, each TF-related consultation was associated with an increase of 0.61 (95% confidence interval 0.15 to 1.06) second-line requests. In this setting, TF-related telephone consultation was positively and significantly associated with diagnosis and reporting of antiretroviral TF.